Relative position in binary substitutions - Coons, Michael; Ramsey, Christopher; Strungaru, Nicolae (My University, 2025)
Given an infinite word on a finite alphabet, an immediate question arises: can we understand the frequency of letters in that word? For words that are the fixed points of substitutions, the answer to this question is often 'yes'—the details and methods of these answers have been well-documented. In this paper, toward a better understanding of the fixed points of binary substitutions, we delve deeper by investigating, in fine detail, the position of letters by defining various position functions and proving results about their behavior. Our analysis reveals new information about the Fibonacci substitution and the extended Pisa family of substitutions, as well as a new characterization of the Thue-Morse sequence.
Keywords: binary substitutions